Analysis of extraocular muscle volumes in idiopathic hypertrophic pachymeningitis patients - Suppakul Kitkamolwat; Supichaya Soonthornpusit; Akarawit Eiamsamarng; Natthapon Rattanathamsakul; Niphon Chirapapaisan; Chanon Ngamsombat (PLoS ONE, 2025)
Background Idiopathic hypertrophic pachymeningitis (HP) is a rare chronic inflammatory condition without an identifiable cause characterized by fibrous thickening of the dura mater, which can involve the extraocular muscles (EOM). Objective To evaluate volumetric changes of EOM in idiopathic HP patients compared with healthy controls (HC) and study the correlation with ocular motility disturbance. Materials and method Twenty-two idiopathic HP patients diagnosed and underwent 3T MRI between 2017 to 2021 at Siriraj Hospital and 22 age- and sex-matched HC were included in this retrospective study. EOM was manually segmented from the T1W image using 3D Slicer software, and volume was calculated using FSL software. T-tests and Mann-Whitney U tests were used to compare EOM volumes between the idiopathic HP and control groups. Pearson’s correlation coefficient was then used to assess the correlation between ocular motility and EOM enlargement. Results In idiopathic HP patients, the average EOM volumes, including the medial rectus (p = 0.002 each), inferior rectus (right p = 0.08, left p < 0.01), inferior oblique (right p = 0.009, left p = 0.005), right lateral rectus (p = 0.005), right superior oblique (p = 0.004), and left superior rectus (p = 0.005) muscles, were significantly larger compared to those in HC, particularly in the left IR and both MR. However, there was no significant correlation between the enlargement of these 9 EOMs and the extraocular movement limitation. Conclusion In idiopathic HP patients, significantly larger EOM volumes were found compared to control subjects. This enlargement could be due to the diffuse infiltrative histopathology potentially involving microstructures in the EOM. Extraocular movement limitations may be related to cranial nerve involvement. However, the enlarged EOM volumes show no significant correlation with extraocular movement limitation.